Pengaruh Sistem Manajemen Berbasis Sekolah dan Kepemimpinan Terhadap Kepuasan Kerja Guru - Damanik, Bahrudi Efendi (Universitas Persatuan Guru 1945 NTT, 2020)
This study aims to determine how the influence of the school-based management system partially on teacher job satisfaction, the influence of leadership partially on teacher job satisfaction and the effect of school-based management systems and leadership simultaneously on teacher job satisfaction. The method used in this study can be classified in associative type research that is a description of complete information about the relationship between variables with other symptoms. Data analysis techniques used in this study are multiple linear regression analysis, classic assumption test, t test, F test and determinant coefficient. The results of the analysis and evaluation of the data obtained that the results of the school-based management system partially have a positive effect on teacher job satisfaction, the leadership variable partially has a positive effect on teacher job satisfaction, the school-based management system variable and leadership simultaneously have a positive effect on teacher job satisfaction. The influence of school and management-based management system variables on job satisfaction by 56.80% means that 43.20% is influenced by other factors not examined.